USE OF FORMATIVE ASSESSMENT IN THE EDUCATIONAL PROCESS OF FUTURE IT TEACHERS - ROMANYSHYNA, Oksana; KARABIN, Oksana (HUMANITARIAN STUDIES: HISTORY AND PEDAGOGY, 2021)
Abstract. The article analyzes and substantiates the aspects of the formative assessment use in the educational process of future informatics teachers, as the reform of the educational paradigm and the modernization of higher education determine the priority directions of its development, actualize scientific research on the use of formative assessment in the educational process of future specialists, substantiate the personalized and student-centered training of students of higher education, highlight the effective implementation of innovative methods and didactic techniques, note the improvement of pedagogical approaches regarding learning and assessment results. In order to effectively use the formative assessment in the educational process of future informatics teachers, we believe that the system of practical assessment should take into account the following: flexible and formative assessment strategies in the context of adaptation to the educational process, diagnosis of achievement at each of the stages of learning, prevention of communication barriers with the team and conditions training, availability of feedback for self-reflection, assimilation of necessary professional competencies for acquisition of significant qualities by future specialists, and development of creative potential. The method of formative assessment of future computer science teachers’ educational achievements is considered as a dynamic and structured system with interconnected components: target, cognitive-active, reflective-creative, evaluation-resultative. The scientific novelty is that the main aspects of formative assessment in the educational process of future informatics teachers have been substantiated and indicated: acquisition by the students of education of fundamental and systematic assimilation of thorough scientific and practical knowledge; development of flexible multifaceted professional potential and stable habits of creative activity; constant expansion of the practical focus on the development of professional abilities; the use of innovative tools and methods of professional development to assess and determine the achievement of goals at each stage of the educational process; implementation of the educational process in cooperation with the stakeholders of educational programs to improve the quality of training of future specialists with the improvement of the positive dynamics of indicators of the quality of higher education. Conclusions. The use of formative assessment in the educational process of future informatics teachers provides unbiased feedback, the implementation of an assessment strategy, allows students to form personal cognitive experience and correct the educational process.